Monitoring Gula Darah sebagai Upaya Pencegahan Diabetes Melitus Tipe 2 pada Populasi Dewasa di Gereja Asisi Jakarta - Yunita, Fenny; Santoso, Alexander Halim; Gunaidi, Farell Christian; Bachri, Fiqi Afrizal; Rafi, Muhammad Adam Abizar (jurnal ABDIMAS Indonesia, 2025)
Diabetes mellitus is a chronic metabolic disease whose prevalence continues to increase due to changes in lifestyle and lack of physical activity, especially in the productive age population. Uncontrolled hyperglycemia can cause various serious complications such as nerve, kidney, vision disorders, and cardiovascular disease. Early detection of blood sugar levels is very important to identify risks early and prevent disease progression. The Community Service Program (PKM) implemented at the Asisi Church, Tebet District, aims to increase public awareness of the importance of early detection of diabetes through blood sugar screening activities. This activity uses the Plan-Do-Check-Act (PDCA) approach, including capillary blood tests with Point-of-Care Testing (POCT) tools and education about risk factors, symptoms, and prevention of diabetes. Of the 68 participants involved, it was found that 10 people (14.7%) had diabetes, 13 people (19.12%) had prediabetes, and 45 people (66.18%) had normal blood sugar levels. These results emphasize the importance of early detection to prevent long-term complications and encourage people to maintain metabolic health in order to improve quality of life sustainably.